2020
DOI: 10.1016/j.eclinm.2020.100650
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pre-exposure prophylaxis (PrEP) regimen use: Switching and discontinuing daily and event-driven PrEP among men who have sex with men

Abstract: Background Optimising HIV pre-exposure prophylaxis (PrEP) provision requires insight into preferences of PrEP regimens and PrEP discontinuation. We assessed regimen switching and discontinuation and their determinants among men who have sex with men (MSM) participating in the Amsterdam PrEP demonstration project. Methods Between 3-August-2015 and 31-May-2016, we enrolled MSM ( n = 374) and TGP ( n = 2) in a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
5
24
1
2
Order By: Relevance
“…This may have affected the choice for edPrEP. Last, reasons for switching between PrEP regimens were assessed separately for AMPrEP [ 6 , 31 ] and Be‐PrEP‐ared [ 20 ], but these data were not included and further analysed in this pooled analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This may have affected the choice for edPrEP. Last, reasons for switching between PrEP regimens were assessed separately for AMPrEP [ 6 , 31 ] and Be‐PrEP‐ared [ 20 ], but these data were not included and further analysed in this pooled analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 42 , 43 Individuals might also switch between daily and event-driven PrEP. 44 Using PrEP during periods of risk reduces overall tenofovir disoproxil fumarate exposure and thus risks of kidney-related adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the AMPrEP study population is a selective group of older, highly educated, white, early PrEP adopters who had been taking PrEP for roughly 4 years before the COVID-19 epidemic, and results may not be generalizable to all MSM taking PrEP. Specifically, this cohort of experienced PrEP users has been extensively counseled in safely starting and stopping PrEP and might, therefore, be more equipped to estimate their HIV risk and change their PrEP use accordingly 21 , 25 compared with recent-initiation PrEP users. Therefore, the results of this study should be confirmed in other groups of PrEP users.…”
Section: Discussionmentioning
confidence: 99%